2013
DOI: 10.1007/s11748-013-0335-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of artificial pneumothorax under two-lung ventilation in thoracoscopic esophagectomy for esophageal cancer in the prone position

Abstract: No excessive increases in airway pressure or clear circulatory depressions were observed because of artificial pneumothorax under two-lung ventilation in thoracoscopic esophagectomy for esophageal cancer in the prone position. These results suggest that artificial pneumothorax under two-lung ventilation is beneficial for maintaining stable hemodynamics and oxygenation in thoracoscopic esophagectomy in prone position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 10 publications
1
23
0
Order By: Relevance
“…Recently, researchers from Japan reported a result of thoracoscopic-esophagectomy for 14 patients in prone position with TLV and artificial pneumothorax, in which they showed a stable perioperative hemodynamics and oxygenation (10). And Bonavina indicated the thoracoscopic esophagectomy in prone position with TLV was a safer and more effective operation procedure by compared to the Ivor Lewis operation (26,27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, researchers from Japan reported a result of thoracoscopic-esophagectomy for 14 patients in prone position with TLV and artificial pneumothorax, in which they showed a stable perioperative hemodynamics and oxygenation (10). And Bonavina indicated the thoracoscopic esophagectomy in prone position with TLV was a safer and more effective operation procedure by compared to the Ivor Lewis operation (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…The TLV with a single-lumen endotracheal tube has rapidly gained popularity and seems to be a promising option for MIE (10,11). However, limited studies have compared the TLV and OLV in patients undergoing thoracoscopic-esophagectomy in a position of semi-prone.…”
Section: Introductionmentioning
confidence: 99%
“…Rino et al (2014) reported that the use of absorbable dense knit hemostat, instead of an electrocautery device, for hemostasis around the RLN could prevent the RLNP during esophageal cancer surgery. Thoracoscopic esophagectomy has been employed as minimally invasive surgery (Saikawa et al 2014;Koyanagi et al 2015). Although magnification of the surgical fields can enable a precise lymph node dissection along the RLN, the advantages of a thoracoscopic esophagectomy for reducing the RLNP continues to be debated.…”
Section: Discussionmentioning
confidence: 99%
“…A recent, larger, randomized controlled trial did however report a reduction in pulmonary complication, including ALI/ARDS, in patients undergoing minimally invasive esophagectomy with lung protective ventilation (5 vs. 8 mL/Kg tidal volume and 5 cmH 2 O positive end‐expiratory pressure) . Another study determined that artificial pneumothorax with maintenance of two‐lung ventilation was both safe and efficacious in the context of thoracoscopic esophagectomy in the prone position …”
Section: Approaches To Reducing Pulmonary Morbidity After Esophagectomymentioning
confidence: 99%